Pemberdayaan Komunitas Peduli Waduk Jlantah melalui Penguatan Literasi Digital untuk Mendukung Promosi Pariwisata Berbasis Komunitas - Moh. Abdul Kholik; Hendri Noviyanto; Cicilia Puji Rahayu; Arma Fauzi; Fahmi Ferdian Dalimarta (Lembaga Pengembangan Kinerja Dosen, 2026)
Jlantah Reservoir in Karanganyar Regency possesses considerable potential as a nature-based tourism destination. Nevertheless, digital media have not been utilized optimally to introduce the destination to broader audiences, resulting in limited dissemination of tourism information. This community service program was designed to enhance the digital literacy competencies of the Jlantah Reservoir Conservation Community (Komunitas Peduli Waduk/KPW) as an effort to strengthen tourism promotion. The implementation adopted a participatory approach consisting of field observation, needs assessment, training, mentoring, and program evaluation. The training materials emphasized social media management, website utilization, digital content development, and digital marketing strategies to improve destination visibility. The outcomes indicate that participants experienced notable improvements in their knowledge and practical skills in managing digital media for tourism promotion. Furthermore, the program fostered stronger collaboration among universities, government institutions, and local communities in promoting sustainable community-based tourism development. Overall, the program provides an initial foundation for expanding tourism promotion, increasing destination attractiveness, and generating positive socio-economic benefits for the surrounding community.